2021
DOI: 10.3390/jcm10153202
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Incidence of Sugammadex-Induced Anaphylaxis Using the Korea Adverse Event Reporting System Database

Abstract: We aimed to investigate the incidence of sugammadex-induced anaphylaxis in a large Korean population. We retrospectively investigated the incidence of sugammadex-induced anaphylaxis between 2013 and 2019 from the database of the Korea Institute of Drug Safety-Risk Management-Korea Adverse Event Reporting System (KIDS-KAERS). We estimated the incidence of sugammadex-induced anaphylaxis from the KIDS-KAERS database, assuming that the reporting efficiency was 10%, 50%, and 100%, respectively. We also investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, since its introduction, adverse effects have remained uncommon and comparable to those associated with other NMBA reversals. In a recent article published by Ju et al [ 32 ], the estimated incidence of sugammadex-induced anaphylaxis was 0.0014%. Furthermore, compared to neostigmine, sugammadex appears to have a decreased incidence of bradycardia in both children and adults [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, since its introduction, adverse effects have remained uncommon and comparable to those associated with other NMBA reversals. In a recent article published by Ju et al [ 32 ], the estimated incidence of sugammadex-induced anaphylaxis was 0.0014%. Furthermore, compared to neostigmine, sugammadex appears to have a decreased incidence of bradycardia in both children and adults [ 15 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis also identified previously well-known predictors for PONV, supporting the reliability of our data. Additionally, considering the increasing use of sugammadex in our institution 14 , we only included patients from 2020 to minimize the effect of possible changes in perioperative management during the study period. A recent meta-analysis reported that compared with neostigmine, sugammadex was significantly associated with a reduction in PONV 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis also identified previously well-known predictors for PONV, supporting the reliability of our data. Additionally, considering the increasing use of sugammadex in our institution 14 , we only included patients from 2020 to minimize the effect of possible changes in perioperative Table 3. Interaction of primary and secondary outcomes between the use of sugammadex (vs neostigmine) and total intravenous anesthesia (vs inhalation anesthesia).…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis also revealed previously well-known predictors for PONV, supporting the reliability of our data. Additionally, considering the increasing use of sugammadex in our institution (Ju et al 2021), we only included patients from 2020 to minimize the effect of possible changes in perioperative management during the study period. A recent meta-analysis reported that compared with neostigmine, sugammadex was signi cantly associated with a reduction in PONV (Hurford et al 2020a).…”
Section: Discussionmentioning
confidence: 99%